Pengaruh Media Sosial, Kualitas Produk, Dan Endorsement Terhadap Keputusan Pembelian Pada Era New Normal - Merni Mutia Rahmi; Dihin Septyanto (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
The purpose of this research is to provide empirical evidence on the effects of social media, product quality, and endorsements on purchase decisions. The independent variables are social media, product quality, and endorsements, and the dependent variable is the purchase decision. To collect data, this research uses the survey method, which involves distributing online questionnaires. Furthermore, the collected data will be analyzed using the Likert scale method, which has six answer options for testing the relationship between variables. Because the population was unknown, the Slovin formula was used in the sampling method. The sample size for this study was 98 respondents, and the following results were obtained: According to the study results, social media has an impact on purchasing decision, product quality has an impact on purchasing decision, endorsement has no impact on purchasing decisions, and social media, product quality, and endorsements all affect the purchase decision all at the same time. This study's analysis is limited to retail companies, specifically PT. Ramayana Sabar Subur Cikupa Branch. As a result, the research findings cannot be generalized to companies in other industries. Based on the study's limitations, the researchers made suggestions including trying to adjust other factors besides endorsement to measure the level of purchasing decisions at the company.